Financing of Education in Brazil: from the literary subsidy to FUNDEB - Carlos Roberto Jamil Cury (Universidade Federal do Rio Grande do Sul, 2018)
This paper aims to describe the evolution of the financing of education in Brazil, especially of basic education (preschool-secondary education). The methodology consisted of investigating the legislation to ascertain how the legal framework incorporated this financing. The study also seeks to highlight advances and setbacks, especially regarding constitutionally earmarked tax revenue for education maintenance and development. Such earmarking began with the Constitution of 1934 and peaked with Constitutional Amendment no. 59 of 2009, which resulted in the National Education Plan in Law no. 13005/2014. One of the most visible points of the evolution is that such earmarking was suppressed under authoritarian or dictatorial regimes and maintained in democratic regimes.